Usefulness of Sōna Aspergillus Galactomannan LFA with digital readout as diagnostic and as screening tool of COVID-19 associated pulmonary aspergillosis in critically ill patients. Data from a multicenter prospective study performed in Argentina. (8th April 2022) - Giusiano, Gustavo; Fernández, Norma B; Vitale, Roxana G; Alvarez, Christian; Ochiuzzi, María Eugenia; Santiso, Gabriela; Cabeza, Matías Sebastián; Tracogna, Fernanda; Farías, Luciana; Afeltra, Javier; Noblega, Luciana María; Giuliano, Carla Valeria; et al.
Abstract: COVID-19-associated pulmonary aspergillosis (CAPA) incidence varies depending on the country. Serum galactomannan quantification is a promising diagnostic tool since samples are easy to obtain with low biosafety issues. A multicenter prospective study was performed to evaluate the CAPA incidence in Argentina and to assess the performance of the lateral flow assay with digital readout (Sōna Aspergillus LFA) as a CAPA diagnostic and screening tool. The correlation between the values obtained with Sōna Aspergillus LFA and Platelia® EIA was evaluated. In total, 578 serum samples were obtained from 185 critically ill COVID patients. CAPA screening was done weekly starting from the first week of ICU stay. Probable CAPA incidence in critically ill patients was 10.27% (19/185 patients when LFA was used as mycological criteria) and 9% (9/100 patients when EIA was used as mycological criteria). We found a very good correlation between the two evaluated galactomannan quantification methods (overall agreement of 92.16% with a Kappa statistic value of 0.721). CAPA diagnosis (>0.5 readouts in LFA) were done during the first week of ICU stay in 94.7% of the probable CAPA patients. The overall mortality was 36.21%. CAPA patients' mortality and length of ICU stay were not statistically different from for COVID (non-CAPA) patients (42.11 vs 33.13% and 29 vs 24 days, respectively). These indicators were lower than in other reports. LFA-IMMY with digital readout is a reliable tool for early diagnosis of CAPA using serum samples in critically ill COVID patients. It has a good agreement with Platelia® EIA. Lay Summary: The incidence of COVID-associated pulmonary aspergillosis (CAPA) in critically-ill Argentinian patients was established (10.27%). Serum galactomannan quantification was useful as a screening tool for this mycosis. A good agreement between Platelia® EIA and Sōna Aspergillus LFA is reported.